EFFECTS OF POULTRY LITTER ON SOIL PHYSICO-CHEMICAL PROPERTIES FOR CROP PRODUCTION IN KAURU LOCAL GOVERNMENT AREA, KADUNA STATE, NIGERIA - Ochai, Matthias I.; Aremu, James K.; Agada, Emmanuel E. (FUDMA Journal of Sciences, 2024)
Poultry litter is an important source of soil nutrients that supports beneficial soil bacteria by serving as a substrate, however, its excessive have adverse effects that lead to soil pollution, contamination and acidification of soil and groundwater. This study analyzed the effects of poultry litter on soil physico-chemical properties for crop production in Kauru Local Government Area, Kaduna State, Nigeria. Data on soil properties at the control and poultry littered sites were collected by sampling four farmlands in Barwa, Ungwan Noma, Kurmin-Shado and Dan-Daura and analyzed in the laboratory. Results were subjected to ANOVA and Correlation analyses tools. The findings revealed significant changes in soil physico-chemical properties due to excessive poultry litter application. Compared to the control site, treated soil showed increased pH (6.26 to 6.89), decreased organic carbon (4.29 to 3.63), increased organic matter (5.92 to 6.99), increased total nitrogen (0.49 to 0.58), altered particle size distribution (clay, silt, sand), reduced aggregate, stability (0.818 to 0.715) and increased CO2 (64.8 to 65.88%). Also, Correlation analysis revealed a significant relationship between poultry litter application and soil physico-chemical properties (Sig. value >0.05), indicating that poultry manure significantly alters soil parameters. The study concludes that while some of the soil properties identified were within safe limits, application of poultry manure altered other properties of the soil. Thus, the study recommends that farmers should use poultry litter in conjunction with other fertilizers and soil amendments to balance nutrient inputs.